Advances in Diagnostic Approaches for Viral Etiologies of Diarrhea: From the Lab to the Field - Malik, Yashpal Singh; Verma, Atul Kumar; Kumar, Naveen; Touil, Nadia; Karthik, Kumaragurubaran; Tiwari, Ruchi; Bora, Durlav Prasad; Dhama, Kuldeep; Ghosh, Souvik; Hemida, Maged Gomaa; Abdel-Moneim, Ahmed S.; Bányai, Krisztián; et al. (Frontiers in Microbiology, 2019)
The applications of correct diagnostic approaches play a decisive role in timely containment of infectious diseases spread and mitigation of public health risks. Nevertheless, there is a need to update the diagnostics regularly to capture the new, emergent, and highly divergent viruses. Acute gastroenteritis of viral origin has been identified as a significant cause of mortality across the globe, with the more serious consequences seen at the extremes of age groups (young and elderly) and immune-compromised individuals. Therefore, significant advancements and efforts have been put in the development of enteric virus diagnostics to meet the WHO ASSURED criteria as a benchmark over the years. The Enzyme-Linked Immunosorbent (ELISA) and Polymerase Chain Reaction (PCR) are the basic assays that provided the platform for the development of several efficient diagnostics such as real-time RT-PCR, loop-mediated isothermal amplification (LAMP), polymerase spiral reaction (PSR), biosensors, microarrays, and next-generation sequencing. Herein, we describe and discuss the applications of these advanced technologies in context to enteric virus detection by delineating their features, advantages, and limitations.